LECTURERS' PERCEPTIONS ABOUT LEARNING TOLERANCE IN ISLAMIC RELIGIOUS LECTURES AT INDONESIA UNIVERSITY OF EDUCATION - Fahrudin Fahrudin; Saepul Anwar (Religio Education, 2022)
This research is motivated by the assumption that lectures of Islamic Religious Education (PAI) in Public Universities (PTU), including Indonesia University of Education (UPI), in various forms, should regulate moderation in religion. Moderation in religion is needed to create a climate of tolerance among students to prevent radicalism and extremism in religion, which is allegedly occurring in public universities. One form of evaluation of PAI lectures at UPI aims to explore the opinions of PAI lecturers at UPI regarding learning in religious lectures they experience. With such a goal, researchers used a quantitative approach with a descriptive-survey method. With the quota sampling technique and considering the sample based on the sample expert's assessment based on the number of lecturers who returned the research questionnaire as many as 16 people with a distribution of 9 senior lecturers and 7 juniors. Because data collection was carried out at one time, the researchers designed a cross-sectional survey design. Collecting data on students 'and lecturers' perceptions regarding tolerance learning in Islamic Education learning at PTU was collected using a Likert scale questionnaire. Meanwhile, the data analysis used descriptive statistics, which are presented in tables and charts. Based on the analysis results, it is possible to judge that lecturers on average (88.19%) have a good perception of learning in Islamic Education lectures at UPI. Thus, there is a lecturer's perception of tolerance learning in Islamic Education lectures at UPI